Предмет: Алгебра,
автор: mk8616194
(х-2)^2-2(х-2)(х+2)+(х+2)^2 СРОЧНООО
gLoYaN:
это упростить надо?
Ответы
Автор ответа:
1
Ответ:
=х^2-4x+4-2x^2-4x+4x+8+x^2+4x+4=16
Объяснение:
Автор ответа:
0
Ответ:
( х - 2 ) ^ 2 - 2 * ( x - 2 ) * ( x + 2 ) + ( x + 2 ) ^ 2 = x ^ 2 - 2 * x * 2 + 2 ^ 2 - 2 * ( x ^ 2 + 2 * x - 2 * x - 2 * 2 ) + x ^ 2 + 2 * 2 * x + 2 ^ 2 = x ^ 2 - 4 * x + 4 - 2 * ( x ^ 2 - 2 * 2 ) + x ^ 2 + 4 * x + 4 = x ^ 2 - 4 * x + 4 - 2 * ( x ^ 2 - 4 ) + x ^ 2 + 4 * x + 4 = x ^ 2 + 4 - 2 * ( x ^ 2 - 4 ) + x ^ 2 + 4 = 2 * x ^ 2 + 8 - 2 * ( x ^ 2 - 4 ) = 2 * x ^ 2 + 8 - 2 * x ^ 2 + 2 * 4 = 2 * x ^ 2 + 8 - 2 * x ^ 2 + 8 = 8 + 8 = 16 ;
Ответ: ( х - 2 ) ^ 2 - 2 * ( x - 2 ) * ( x + 2 ) + ( x + 2 ) ^ 2 = 16.
Объяснение:
Похожие вопросы
Предмет: Английский язык,
автор: elinakru152
Предмет: Алгебра,
автор: victoria46
Предмет: Русский язык,
автор: dzgoeva88
Предмет: Русский язык,
автор: saniyamuratova
Предмет: Математика,
автор: polino4ka07191